(untitled) (Research, Society and Development, 2024)
The Port of Santos is considered the largest in the country and one of the main in the world. Port activities can cause negative socio-environmental impacts, and effects on the air quality are one of them. The objective of this research was to quantify the emission of NOx into the air from ship traffic in the Port of Santos, analyze whether NOx emitted by ships is detected at the CETESB air quality analysis station located in Ponta da Praia, in the municipality of Santos, and evaluate the occurrence of health events related to respiratory diseases in this municipality. The emission of nitrogen oxides (NOx), from ship traffic in the Port of Santos, was calculated from January 2021 to February 2022. The accumulated monthly NOx measurement was collected at the CETESB station “Santos – Ponta da Praia”, from January 2021 to December 2022. In the same period, the occurrence of respiratory system health events (ICD-10) was verified in the municipality of Santos by DATASUS. A strong correlation was evidenced between the number of berthings, especially solid bulk cargo, and NOx emissions. Health events related to respiratory diseases, such as bronchitis and emphysema, in Santos showed a moderate and significant correlation with NOx concentration. A moderate correlation was identified between NOx and the occurrence of health events in the child and youth population. These findings are important for understanding the relationship between air pollution and respiratory diseases in the Port of Santos region.